Effects of Moisture and Direction of Grain on the Thermal Conductivity and Mechanical Properties of Black Alder and Scots Pine - Kurt, Şeref; Korkmaz, Mustafa (Kastamonu University, 2022)
Aim of study: Relationships between moisture content and thermal conductivity and mechanical properties of wood species were examined. Material and methods: Black Alder (Alnus glutinosa L.) and Scots Pine (Pinus sylvestris L.) specimens were used. Thermal conductivity, modulus of rupture, compression strength and impact bending strength values were determined and analyzed. All specimens were examined at 3 different moisture levels which are oven-dry, fiber saturation point (FSP) and completely wet. Main results: The lowest thermal conductivity value was found in the perpendicular to the grain direction of oven dried Black Alder samples as 0.119 W/mK. The highest thermal conductivity value was found in the parallel direction of Scots pine samples with FSP humidity content as 0.340 W/mK. In addition, the thermal conductivity value parallel to the grain is significantly higher than perpendicular one at all three moisture levels. Highlights: While there is a positive linear relationship between the moisture content of the wood and its dynamic bending resistance and thermal conductivity; It was found that there is a negative linear relationship between bending strength and compressive strength value.
Keywords: Isı İletkenliği; Nem Miktarı; Lif Yönü; Çarpmada Eğilme Dayanımı; Diffusivity; Thermal Conductivity; Moisture Content; Grain Direction; Impact Bending Strength; Thermal Conductivity; Moisture Content; Grain Direction; Impact Bending Strength